The Effort to Improve Water Quality of the Pemandian Alam Tourism in Batu Mbelin Village, North Sumatera - Yanqoritha, Nyimas; Sinurat, Serepita; Kuswandi; Handayani, Meyga Fitri; Sulhatun; Suryati (Research and Social Study Institute, 2022)
The purpose of monitoring the water quality of Deli River at the Pemandian Alam in Mbelin Village, Sibolangit District was an effort to ensure that the Deli River at the meeting point of the Lau Betimus and Lau Petani were a Natural Bath that is safe from pollution. At the confluence point of the Lau Betimus and Lau Petani, it was observed based on the pollution index described by each station from upstream to downstream. The Deli River Pollution Index at the monitoring point of the Lau Betimus and the confluence of the Lau Petani were 0.49 and 0.55, which means the water quality is in good condition index or meets the quality standard. This means that the water quality at the observation station is still natural and has not been polluted by pollutants or waste.